A renewed look at legal research: epistemological precisions - Lavado Mallqui, Lucas (2022)
It is an approach to research in law from an epistemological perspective, emphasizing those central aspects such as background, problems, theories, hypotheses and their contrast. The purpose of this article is to try to analyze some difficulties through some texts that circulate in Peruvian universities based on how law lessons are designed and taught.